The Synthesis of The Word "Bahrain" and Scientific Proof in Tafsir Ilmi by Ministry of Religion: Sistesis Kata “Bahrain” dan Pembuktian Sains dalam Tafsir Ilmi Kementerian Agama (Takwil: Journal of Quran and Hadith Studies, 2023)
This research is motivated by new discoveries related to natural phenomena but have long been explained by the Qur'an. The phenomenon of the meeting between two sea waters either vertically or horizontally but not mixed between them was one of the phenomena that has been mentioned in the Qur'an. The purpose of this research is to look more broadly at the explanation of the phenomenon of the meeting of the two seas both in the perspective of the Qur'an, the mufasirs and in the view of science. From this study found the results 1) the word bahrain refers to two meanings. Firstly, it refers to the meeting of two sea waters that are both salty but the level of saltiness between the two is different. While the second, refers to the notion of a meeting between fresh water (river) and salt water (sea). 2) In general, the scholars of interpretation argue that what is meant by the word bahrain in the Qur'an is the meeting between fresh water and salt water, both of which flow side by side but do not mix with each other because of the boundaries created by Allah SWT, which cannot be seen by human eyes. 3) According to the scientific interpretation of the Ministry of Religious Affairs, it is said that Allah has made two different seas, one fresh and the other salty. Both move next to each other but do not mix with each other. This is one of the favours that Allah gives to humans. In the research that has been done, experts who focus on the ocean managed to find the boundary between two different seas. The discovery revealed that there is a dividing line between each sea, which flows between the two seas. The dividing boundary is called a front.